Fast synthesis and energy transfer of the tunable single-phase white-emitting phosphor Li2Gd4(WO4)7:Dy3+, Tm3+ for WLEDs. Issue 5 (1st April 2020) - Fan, Minghan; Liu, Shuo; Yang, Kai; Guo, Jia; Wang, Junxian; Wang, Xuhong; Liu, Quan; Wei, Bo
Abstract: A series of Dy 3+ and Tm 3+ co-doped Li2 Gd4 (WO4 )7 (LGW) single-phase white phosphors were fast synthesized by microwave assisted solid-state reaction method. Single-ion doped LGW:Dy 3+ and LGW:Tm 3+ phosphors were synthesized to obtain quenching concentrations. The ideal white light (0.33, 0.33) locates on the straight line that connects the Commission Internationale de L'Eclairage (CIE) coordinates of LGW:Dy 3+ and LGW:Tm 3+ . Therefore, Dy 3+ and Tm 3+ were selected to co-dope LGW to realize white light emission. By changing Dy 3+ concentration, white light was obtained under the excitation wavelengths of 356 nm and 363 nm. Luminescence decay curves and the emission spectra of the co-doped phosphors were characterized to verify the existence of energy transfer between Tm 3+ and Dy 3+ in this single-phase phosphor. Energy transfer efficiency and energy transfer mechanism were investigated in detail. This fast synthesized single-phase white phosphor LGW:Dy 3+, Tm 3+ is a good candidate for the white light emitting diodes.